Management Excellence ; Sebuah Pendekatan Praktis Untuk Membangun Organisasi Yang Excellent - Weni Novandari (P4M STIE Putra Bangsa, 2014)
The concept of management continues to evolve over time. New concepts in management replace the previous concepts that are not relevant anymore with the recent condition. One thing to be observed is that the concepts of management should not merely a collection of principles, procedures, methods and techniques, but the concept should be operationalized, so it can be implemented by the organization. This article discusses about how to become an excellent organization with the implementation of management excellence. Organizational excellence itself is a manifestation of the concept of total quality management. By applying excellence management, organization will be able to understand the changes and quickly adapt even utilize the changes into the source of their advantage. Organizations are able to understand and align the needs of all stakeholders , able to anticipate the market movements, and capable of interpreting trends will come and the current condition of the well so that the organization can enhancing their performance and achieve long-term excellence.